2D Heterostructure of Bi2O2Se/Bi2SeOx Nanosheet for Resistive Random Access Memory. (27th April 2022) - Xia, Yan; Wang, Jing; Chen, Rui; Wang, Hongbo; Xu, Hang; Jiang, Changzhong; Li, Wenqing; Xiao, Xiangheng
Abstract: 2D materials have shown great potential in the application of resistive random access memory (RRAM) for information storage. Much attention has been attracted from 2D semiconducting bismuth oxyselenide (Bi2 O2 Se) for excellent properties in multi‐performance nanoelectronics. By using a chemical vapor deposition (CVD) method, Bi2 O2 Se nanosheets with high quality are grown. Combining with the oxygen plasma method, 2D heterostructure of Bi2 O2 Se/Bi2 SeO x nanosheet is realized; and the heterostructure exhibits obvious resistive switching behavior. The resistive switching mechanism is analyzed in detail, and the conductive mechanism of the fabricated device is also discussed. The resistive switching of Bi2 O2 Se nanosheets is endowed through the method of O2 plasma treatment, which makes it feasible for developing its application in the RRAM. Abstract : 2D Bi2 O2 Se has attracted much interest in electronics and optoelectronics. Here, to explore the application of Bi2 O2 Se in resistive random access memory (RRAM), Bi2 O2 Se nanosheets are grown by chemical vapor deposition, and a 2D heterostructure is constructed by oxygen plasma treatment. Obvious bipolar resistive switching behavior is realized in Bi2 O2 Se‐based memory, which demonstrates its great potential in RRAM.